Balancing human–bear coexistence with biodiversity conservation. Issue 2 (4th March 2023) - Su, Kaiwen; Yang, Jie; Lin, Lin; Hou, Yilei; Wen, Yali
ABSTRACT: Human–bear conflicts (HBC) impact the livelihoods and safety of local communities in underdeveloped areas and challenges local governments and wildlife conservation agencies. We conducted a systematic analysis of HBC in the Sanjiangyuan National Park, which is a core region of the Qinghai Tibet Plateau. This study consisted of semi-structured interviews with 81 stakeholders in October 2020, including local families and government departments. We qualitatively assessed the dominant characteristics and causes of bear damage in the region and proposed various mitigation strategies. The results revealed that recent implementations of biodiversity conservation and ecological restoration policies have increased the number and severity of HBC. Livestock depredation, attack on humans, and house break-ins were the most common and damaging conflict types. We discuss the challenges of HBC mitigation in the region and propose possible mitigation strategies based on the results of the interviews.